Enhancing competitiveness of Muslim clothing SMEs through entrepreneurial orientation and product innovation - Fatmah, Dinda; Rahmah, Mirhamida; Aslikhah, Nurul; Soe, Htet Paing; Rahmah, Yusriyah (Faculty of Business & Economics, Universitas Islam Indonesia, 2024)
Purpose – This study aims to explore the relationships between entrepreneurial orientation (EO), market orientation, product innovation, and competitive advantage within Muslim clothing SMEs. This study provides insights into how these factors interact and contribute to the overall success of these enterprises.Methodology – This quantitative study explores the relationships between entrepreneurial orientation, market orientation, product innovation, and competitive advantage in the Muslim clothing industry. Using a proportional sample of 103 employees from Muslim clothing SMEs in East Java, data were collected through a five-point Likert-scale questionnaire and analyzed via multiple regression to assess direct and mediating effects.Findings – The key findings reveal that entrepreneurial orientation positively impacts product innovation, indicating that entrepreneurial companies are more innovative. Additionally, EO significantly influences market orientation, making firms more responsive to their market needs. EO enhances competitive advantage, whereas market orientation negatively impacts it, suggesting that excessive focus on the market may hinder differentiation. Conversely, product innovation positively affects a firm’s competitive advantage. The study finds that market orientation does not mediate the relationship between EO and competitive advantage, whereas product innovation does.Implications – These findings provide practical insights for SMEs in the Muslim clothing industry. Companies should cultivate entrepreneurial orientation to boost innovation and competitive advantage, balancing market orientation to avoid stifling differentiation. Originality – This study contributes to the literature by investigating the intricate relationships between EO, market orientation, product innovation, and competitive advantage in Muslim Clothing SMEs, emphasizing the mediating role of product innovation.